1994
DOI: 10.3354/meps104211
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology and condition of larval and pelagic juvenile redfish Sebastes spp.

Abstract: ABSTRACT. Eggs and nauplii of Calanus finmarchicus were the preferred prey types of redfish larvae whereas Oithona spp. copepodites were not, even though they were within the preferred size range. Significant seasonal and annual differences in larval diet of redfish resulted from differences in the availability of preferred prey. Seasonally, feeding was related to the succession of the spring dominance of C. finmarchicus to summer dominance of Oithona spp. Interannually, feeding was related to differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 38 publications
0
44
0
2
Order By: Relevance
“…Herbivory studies, on their part, have frequently revealed extensive herbivory on flowers or developing fruits, a situation particularly frequent among perennial herbs such as H. foetidus (37)(38)(39)(40)(41). Nevertheless, reductions in seed production with respect to some maximum potential value due to herbivores or insufficient pollination do not necessarily have to influence plant population dynamics, because seed production may exceed the habitatspecific requirements for maintaining average plant density (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbivory studies, on their part, have frequently revealed extensive herbivory on flowers or developing fruits, a situation particularly frequent among perennial herbs such as H. foetidus (37)(38)(39)(40)(41). Nevertheless, reductions in seed production with respect to some maximum potential value due to herbivores or insufficient pollination do not necessarily have to influence plant population dynamics, because seed production may exceed the habitatspecific requirements for maintaining average plant density (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Both circumstances seem to be particularly common among herbaceous plants, which frequently experience devastating levels of flower and fruit herbivory (3, 37-41, 48, 49) by insect and mammalian herbivores that tend to be quite selective and concentrate on individuals with the larger floral displays and蜑or fruit crops (17,18,41,50). We hypothesize that adaptive correlated evolution of mutualism-and antagonismrelated driven by correlational selection should be particularly frequent among herbaceous plants.…”
Section: For P Broteri)mentioning
confidence: 99%
“…Daily ration estimates, as percent of gut-free body weight, given for minimum and maximum daylight lengths (duration of feeding) when billfish larvae are present during the protracted spawning season of approximately April to November trary to many studies that show a more constant increase in prey size, usually including shifts from copepod eggs and nauplii to calanoid copepodids and larger adults (e.g. Anderson 1994, Pepin & Penney 1997. Perhaps the most advanced first-feeding larvae are the coastal mackerels Scomberomorus spp.…”
mentioning
confidence: 99%
“…Thus, their presence in numbers of zooplankton could have a serious effect on the recruitment of larval fish and could be very significant for the fish stocks and for the fishing industry. Houde and Lovdal (1982), Balbontin et al (1986) and Anderson (1994) presented that small zooplankton e.g. Copepods, Tintinnids, Cladocerans, larval molluscs etc.…”
Section: Discussionmentioning
confidence: 99%